2022
DOI: 10.1177/23259671221142257
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Bankart Repair With Remplissage as an Alternative to Latarjet for Anterior Glenohumeral Instability With More Than 15% Glenoid Bone Loss

Abstract: Background: Surgical management of anterior shoulder instability continues to evolve. The clinical effectiveness of arthroscopic Bankart repair with remplissage (REMP) in patients with increasing glenoid bone loss (GBL) has not been thoroughly compared with Latarjet. Purpose/Hypothesis: The purpose of this study was to compare 2-year outcomes of REMP versus open Latarjet in patients with >15% GBL. We hypothesized that there would be no difference. Study Design: Cohort study; Level of evidence, 3. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Mean follow-up length varied across the studies from 24.7 to 74 months; follow-up length was not always similar between groups and not always separately reported for BR and Latarjet groups. All studies reported recurrence; while 4 studies 1 , 18 , 19 , 38 only reported recurrent dislocations, the other studies 4 , 11 , 22 , 40 reported recurrent instability. Preoperative ISI score was reported in 3 of the reviewed articles 4 , 11 , 40 with a mean value of 4.4 in the BR group and a mean value of 4.7 in the Latarjet group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean follow-up length varied across the studies from 24.7 to 74 months; follow-up length was not always similar between groups and not always separately reported for BR and Latarjet groups. All studies reported recurrence; while 4 studies 1 , 18 , 19 , 38 only reported recurrent dislocations, the other studies 4 , 11 , 22 , 40 reported recurrent instability. Preoperative ISI score was reported in 3 of the reviewed articles 4 , 11 , 40 with a mean value of 4.4 in the BR group and a mean value of 4.7 in the Latarjet group.…”
Section: Resultsmentioning
confidence: 99%
“… 1 , 4 , 11 , 40 Recent literature comparing BR and the Latarjet procedure in patients with a glenoid bone loss greater than 15% has shown similar recurrent instability rates. 18 While, BR has shown less recurrent instability than the Latarjet procedure in a study with a mean glenoid bone loss below 15%. 19 Contrastingly, the study of Hurley et al 22 showed reduced recurrent instability in the Latarjet group compared to the BR group.…”
mentioning
confidence: 89%
“…Hurley et al [28] found higher rates of recurrent instability following ABR alone (16.8%) compared to OLP (7.0%) and ABR with remplissage (3.2%). A study by Horinek et al [20] compared OLP with ABR with remplissage, for anterior shoulder instability and found no difference in terms of clinical scores, return to sport, and satisfaction. In the present meta-analysis, only one study performed arthroscopic bony Bankart repair with remplissage (in 11 of 312 patients) [47] but did not report the outcomes of this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the results suggesting the supremacy of Latarjet over arthroscopic, soft tissue-only repairs, Horinek et al recently demonstrated that ABR and remplissage yields similar 2 year outcomes to Latarjet in patients with >15% GBL ( 52 ). This lead the authors to conclude that remplissage is a consideration in patients with GBL >15% and it is notable that their cohort includes patients well beyond subcritical bone loss thresholds, with mean GBL in both groups of 25%.…”
Section: Surgical Management Of Subcritical Bone Lossmentioning
confidence: 93%